Synergistic Reduction of TNF-α by Combined Ursodeoxycholic Acid and Multi-Strain Probiotics in a Rat Model of Cholestasis - Muhammad Hasbi Nur; Erik Prabowo; Sigit Adi Prasetyo (HM Publisher, 2026)
Background: Cholestasis is a complex hepatobiliary disorder in which impaired bile flow provokes a sustained inflammatory response, with tumor necrosis factor-alpha (TNF-α) acting as a central pro-inflammatory mediator. Ursodeoxycholic acid (UDCA) is the first-line therapy, but a substantial subset of patients responds incompletely, motivating adjunctive strategies that target extrahepatic, gut-derived drivers of inflammation through the gut–liver axis. Objective: To evaluate whether multi-strain probiotics potentiate the anti-inflammatory (TNF-α–lowering) effect of ursodeoxycholic acid (UDCA) in experimental cholestasis. Methods: This randomised, post-test-only controlled experimental study was reported in accordance with ARRIVE 2.0 guidelines. Thirty-five male Sprague-Dawley rats were randomised into seven groups (n=5): healthy control (K1), disease control (K2), UDCA monotherapy (K3), probiotic monotherapy (K4), and three UDCA plus dose-escalating probiotic combinations (K5–K7). Cholestasis was induced by common bile duct ligation; interventions ran for 21 days. Serum TNF-α was quantified by ELISA and analysed with one-way ANOVA, Tukey HSD and Games-Howell post hoc tests, effect sizes, and dose-response regression. Results: TNF-α differed markedly across groups (F(6,28)=783.5, p<0.001, η²=0.994). Ligation raised TNF-α from 5.69±0.25 pg/mL (K1) to 17.88±0.43 pg/mL (K2; p<0.001, Cohen's d=34.7). Both monotherapies reduced TNF-α (K3 14.91±0.49; K4 12.50±0.32; both p<0.001), but combination therapy achieved significantly greater suppression, lowest in K7 (7.91±0.18 pg/mL; 55.8% reduction; 81.8% normalisation toward healthy). A significant dose-dependent decline occurred across combination groups (slope=−0.113 pg/mL per mg, r=−0.94, R²=0.89, p<0.001). Conclusion: Combined UDCA and probiotics produce a synergistic, dose-dependent reduction of TNF-α in experimental cholestasis, supporting probiotics as a rational adjunct targeting the gut–liver axis and warranting translational evaluation in cholestatic patients.